Digital media use and its effects on digital eye strain and sleep quality in adolescents: A new emerging epidemic? - Merve Şambel Aykutlu; Hasan Cem Aykutlu; Mehmet Özveren; Rüveyde Garip (PLoS ONE)
This study examines the association between excessive digital media use and adverse health outcomes, specifically Digital Eye Strain (DES) and Poor Sleep Quality (PSQ), in adolescents. A cross-sectional survey of 512 participants (aged 11-18 years) assessed DES and PSQ using the Computer Vision Syndrome Questionnaire and the Pittsburgh Sleep Quality Index. We found a high prevalence of DES (63.7%) and PSQ (51.2%). Factors associated with DES included using digital media for more than two hours daily, increased post-pandemic digital consumption, shorter breaks, and PSQ. Extended daily digital media use (>4 hours), bedtime usage, older age, female sex, online education and DES were significantly associated with PSQ. These findings highlight the harmful effects of excessive digital media use on adolescent health, especially post-COVID-19. The intricate link between DES and PSQ underscores the need for public health interventions to promote healthy digital habits.